Combined fit of spectrum and composition data as measured by the Pierre Auger Observatory - Aab, A.; Abreu, P.; Aglietta, M.; Al Samarai, I.; Albuquerque, I. F. M.; Allekotte, Ingomar; Almela, Daniel Alejandro; Alvarez Castillo, J.; Alvarez Muñiz, J.; Anastasi, G. A.; Anchordoqui, Luis A.; Andrada, Betiana Eugenia; et al. (IOP Publishing, 2017)
Fil: Aab, A.. Radboud Universiteit Nijmegen; Países Bajos